The Repetition Drill in Teaching Simple Present Tense - Tirza Kumayas (Jurnal Lingua Idea, 2022)
This research was the description of an attempt to find out the effective technique to overcome the students' problem in using verbs which deal with the third person singular in the simple present tense correctly. To solve the problem above, he used repetition drill as a technique. The method of this research is pre-experimental descriptive method with one pre-test and post-test. The population was the students in second year at English Education Department and the sample consisted of 34 students. According to the result of this research the writer used the statistic instrument in analyzing the obtained data. And the finding shows that the result of the mean score of pre-test is 4.06 and the mean score of post-test is 7.05; this means that the result of post-test is much better than the pre-test. It can be concluded that the use of Repetition drill technique was effectively to solve the students' problem. The writer suggested that English teachers use repetition drill in teaching to increase the students' mastery in using verbs which deal with the third person singular in simple present tense. Keywords: Repetition Drill, Teaching, Simple Present Tense